Performance Series Performance Metrics (*) A case study in the General Company for Cotton Industries - داود, غسان قاسم; سلمان, كاظم داود (Journal of Economics and Administrative Sciences, 2009)
The problem of the research is focused on importance limited of Iraq industrial companies in application of scientific measurements of supply chains performance,  The research sought to achieve a group of goals, the most important are , identifying the strengths and weaknesses in the reality of supply chain in General Company for Cotton Industries, The data and information required are gathered from the dependence company, records through the field observations and personal interviews, the research used some quantitative indicators to measure of supply chain performance, The research reached to many conclusions , the most outstanding among them is the existence of a strong inverse correlation between the total of supply chain variables, the study presented a group of recommendations to the company studied that represent, building of close relationship with suppliers and taking the correct procedures supply and attention to the sale and distribution outlets.